QRIS-Based Digital Marketing: Collaborative Strategies between Merchants and Financial Service Providers - Waqiah; Misfah Muslimawati; Farhatun Zaidah (PT. Anagata Sembagi Education, 2025)
This study aims to analyze the implementation of the Quick Response Code Indonesian Standard (QRIS) as a collaborative digital marketing strategy between merchants and financial service providers in Indonesia. Using a descriptive qualitative approach, this research explores the relationship between QRIS adoption, business collaboration, and its impact on transaction efficiency and MSME competitiveness in the digital economy. Data were collected through semi-structured interviews with MSME owners from the retail, culinary, and service sectors, as well as representatives from financial institutions involved in the QRIS ecosystem. The findings reveal that QRIS integration enhances transaction efficiency, strengthens consumer trust, and expands market access for small businesses. The collaboration between merchants and financial providers creates shared value through the utilization of transaction data as a foundation for marketing decision-making. Moreover, QRIS contributes to accelerating financial inclusion and reducing digital inequality across regions. Nonetheless, challenges remain, particularly in addressing limited digital literacy and infrastructure in rural areas. This study concludes that QRIS functions not only as a financial innovation but also as a strategic instrument for developing an inclusive, efficient, and sustainable digital marketing ecosystem for MSMEs in Indonesia.